Comparison of efficacy of multimatrix mesalazine 4.8 g/day once-daily with other high-dose mesalazine in active ulcerative colitis: a randomized, double-blind study - Ogata, Haruhiko (Intest Res, 2017)
BACKGROUND/AIMS: This study assessed the efficacy and safety of high-dose multimatrix mesalazine once-daily (QD) compared to another form of high-dose mesalazine. METHODS: In this multicenter, randomized, double-blind study, 280 patients with mildly to moderately active ulcerative colitis (UC) received multimatrix mesalazine 4.8 g/day QD or pH-dependent-release mesalazine 3.6 g/day three times daily for 8 weeks. The primary endpoint was the change in the UC-Disease Activity Index (UC-DAI) at the end of the treatment period. RESULTS: The change in the UC-DAI (mean±standard deviation) in the per-protocol set was −2.6±2.47 in the multimatrix mesalazine 4.8 g/day group (n=134) and −1.8±2.64 in the pH-dependent-release mesalazine 3.6 g/day group (n=129). The difference in the mean change between the 2 groups was −0.7 (two-sided 95% confidence interval, −1.3 to −0.1). The noninferiority of multimatrix mesalazine 4.8 g/day to pH-dependent-release mesalazine 3.6 g/day was verified within the noninferiority margin (1.1). The superiority of multimatrix mesalazine 4.8 g/day to pH-dependent-release mesalazine 3.6 g/day was also investigated and confirmed in the full analysis set, according to the study protocol. In subgroup analyses, the effectiveness of multimatrix mesalazine 4.8 g/day was consistent in all subgroups. There was no difference in safety between the 2 treatment groups. CONCLUSIONS: Multimatrix mesalazine 4.8 g/day has higher efficacy and shows no difference in safety in mildly to moderately active UC, in comparison with pH-dependent-release mesalazine 3.6 g/day.